2021
DOI: 10.3390/su13169210
|View full text |Cite
|
Sign up to set email alerts
|

The Nexus between Tourism Activities and Environmental Degradation: Romanian Tourists’ Opinions

Abstract: This paper aims to analyse the nexus between tourism activities, including tourists’ circulation, accommodation or entertainment, and environmental degradation. Consequently, the conceptual framework captures the complexity of the nexus between tourism and the environment, given that tourism activities can be performed by tourists or for tourists and that tourism depends on the environmental quality, and, consequently, we highlight the impact of tourism activities on biodiversity loss through the pollution eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 99 publications
0
13
0
1
Order By: Relevance
“…The attempt to define an absolute green purchasing profile and consumption for Generation Z is still being observed and analyzed, because the reactions, personal implications, affinities, perceptions are not stabilized in order to be able to build a standard profile, but what is clearly reflected until now confirms the fact that we are talking about a more mature, conscious, economical generation, with an emphasis on the principles of a healthy life, in agreement with the norms of environmental protection. The first years of professional activity for Generation Z largely coincided with the onset of the COVID-19 pandemic, which influenced certain components of their natural behavior, given the state of uncertainty experienced, with multiple emotional connotations (Butnaru et al, 2021). The coming years will be able to stabilize the behavior, perception and profile of the Generation Z consumer of green products, including the exact determination of the impact of green marketing practices.…”
Section: Theotetical Contributionsmentioning
confidence: 99%
“…The attempt to define an absolute green purchasing profile and consumption for Generation Z is still being observed and analyzed, because the reactions, personal implications, affinities, perceptions are not stabilized in order to be able to build a standard profile, but what is clearly reflected until now confirms the fact that we are talking about a more mature, conscious, economical generation, with an emphasis on the principles of a healthy life, in agreement with the norms of environmental protection. The first years of professional activity for Generation Z largely coincided with the onset of the COVID-19 pandemic, which influenced certain components of their natural behavior, given the state of uncertainty experienced, with multiple emotional connotations (Butnaru et al, 2021). The coming years will be able to stabilize the behavior, perception and profile of the Generation Z consumer of green products, including the exact determination of the impact of green marketing practices.…”
Section: Theotetical Contributionsmentioning
confidence: 99%
“…Sumberdaya ekowisata terdiri dari sumberdaya alam dan sumberdaya manusia yang dapat diintegrasikan menjadi komponen terpadu bagi pemanfaatan wisata [13]. Berdasarkan konsep pemanfaatan, wisata dapat diklasifikasikan menjadi Wisata alam (nature tourism), merupakan aktivitas wisata yang ditujukan pada pengalaman terhadap kondisi alam atau daya tarik panoramanya, Wisata budaya (cultural tourism), merupakan wisata dengan kekayaan budaya sebagai obyek wisata dengan penekanan pada aspek pendidikan, Ekowisata (ecotourism, green tourism), merupakan wisata berorientasi pada lingkungan untuk menjembatani kepentingan perlindungan sumberdaya alam / lingkungan dan industri kepariwisataan [14].…”
Section: Keberlangsunganunclassified
“…The nexus between tourism and the environment is very complex [34]. Some studies have demonstrated that tourism had a significantly negative impact on CO 2 emissions in both long and short perspective [35,36].…”
Section: Literature Review 21 Impact Of Tourism On Co 2 Emissionsmentioning
confidence: 99%
“…Although there are still controversies about the relationship between tourism and carbon emissions in empirical research, the academic community basically recognizes the direct impact of tourism sectors in promoting carbon emissions. Tourism transport is the most vital polluting sources [6,40,41], and tourism activity as well as the accommodation sector are also the important sources of carbon emissions [34,42,43]. For instance, a global estimation by UNWTO-UNEP-WMO [1] reported that the share of tourism in global CO 2 emissions was at 4.9%, among which 75% was derived from tourism transport.…”
Section: Literature Review 21 Impact Of Tourism On Co 2 Emissionsmentioning
confidence: 99%